Fundamentos de los manuales de identidad universitaria para la responsabilidad social - Camacho Domínguez, Adriam (2020)
This paper is contextualized within the framework of Latin American and Ecuadorian higher education starting from the identity crises of the university communities taking into account elements such as the loss of values, the lack of clarity of the missions, visions and institutional philosophies. Precisely aims to analyze the manuals of image and / or corporate identity and / or university as work tools and guidance to position and strengthen the processes of internalization and externalization of historical and identity elements. The methodology used was based on the qualitative approach in which theoretical methods such as analysis-synthesis, inductive-deductive and historical logic predominated from a ypology of documentary, comparative and explanatory research. The analysis of content and institutional discourse was used from a rational and planned perception of the images and texts included in the sample of the manuals analyzed from a total of ten universities, six Latin American and four Ecuadorian. The fundamental results allowed identifying the flaws existing in the conception of the university identity from its diverse expressions, generating partial conceptions in the manuals that focus more on ordering the communicational, symbology and image aspects.